Bee pollen peptides as potent tyrosinase inhibitors with anti-melanogenesis effects in murine b16f10 melanoma cells and zebrafish embryos - Papassara Sangtanoo; Piroonporn Srimongkol; Tanatorn Saisavoey; Songchan Puthong; Anumart Buakeaw; Rutairat Suttisuwan; Marisa Jatupornpipat; Wittaya Pimtong; Onrapak Reamtong; Aphichart Karnchanatat (Scientific Reports)
Abstract One important functional food ingredient today, valued for its health properties and ability to prevent disease, is bee pollen, which comprises a combination of nectar, pollen from plants, and the secretions of bees. In this research, the tyrosinase (TYR) inhibiting abilities of the peptides derived from bee pollen protein hydrolysates are investigated. Various proteases were utilized to generate these peptides, followed by testing at different concentrations. Tyrosinase inhibition activity was detected in all cases, while the hydrolysate drawn from 5.0% w/v neutrase exhibited the best IC50 value and was thus investigated further via ultrafiltration to separate the active fractions. The highest potential for tyrosinase inhibition was recorded for the fractions below 0.65 kDa. Subsequent purification steps via SEC and RP-HPLC led to the identification of the VDGYPAAGY (named VY-9) peptide via LC-Q-TOF-MS/MS in fraction F1–2, known for its non-toxic and hydrophobic characteristics albeit poor water solubility. The synthesized VY-9 peptide demonstrated competitive inhibition, with IC50 values of 0.55 ± 0.03 µM for mono-phenolase and 2.54 ± 0.06 µM for di-phenolase activities, as confirmed by molecular docking analysis revealing dominant hydrogen bond interactions with TYR. Effective concentrations of 0.2–1.6 µM of VY-9 showed negligible cytotoxicity in B16F10 cells. Melanin synthesis suppression was examined via qRT-PCR, and western blot in MITF, TYR, TRP-1, and TRP-2. Cell death in zebrafish embryos was evaluated in vivo using a toxicity assay which revealed no significant influence from VY-9, while anti-melanogenic effects were observed when the concentration was 4 µM, suggesting bee pollen-derived peptides’ potential in cosmetic and pharmaceutical depigmentation applications.